2011
DOI: 10.1117/1.3575647
|View full text |Cite
|
Sign up to set email alerts
|

Regional tissue oxygen saturation: comparability and reproducibility of different devices

Abstract: Abstract. Comparability and reproducibility of different near-infrared spectroscopy devices measuring regional tissue oxygen saturation remain poor. Aim of the present study was to compare values and reproducibility of cerebral/peripheral "tissue-oxygenation-index" (TOI; NIRO 300, Hamamatsu R , Japan) with cerebral/peripheral "regional-oxygen-saturation" (rSO; INVOS5100, Somanetics R , USA), and to analyze the influence of quality criteria. Methods: cTOI and crSO2 were measured on the left forehead, pTOI and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
49
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 26 publications
5
49
1
4
Order By: Relevance
“…For instance the NIRO 300 and INVOS 4100/5100 adult sensor have been compared several times showing comparable mean values during steady state, but all studies had very few if any rStO 2 values below 50% [38][39][40][41]. Regarding the difference between the INVOS adult and pediatric sensors, Dullenkopf et al found a similar mean difference of 11.3 ± 5.37% (SD) between the two sensors, while Pocivalnik found a mean difference of 10% between the NIRO 300 and the INVOS neonatal sensor [42], that has been shown to give similar values to the paediatric sensor [43]. It is thus certain that despite same sensor geometry and LED wavelengths, the INVOS adult sensor gives systematically lower values than the comparable neonatal and paediatric sensors.…”
Section: Discussionmentioning
confidence: 70%
“…For instance the NIRO 300 and INVOS 4100/5100 adult sensor have been compared several times showing comparable mean values during steady state, but all studies had very few if any rStO 2 values below 50% [38][39][40][41]. Regarding the difference between the INVOS adult and pediatric sensors, Dullenkopf et al found a similar mean difference of 11.3 ± 5.37% (SD) between the two sensors, while Pocivalnik found a mean difference of 10% between the NIRO 300 and the INVOS neonatal sensor [42], that has been shown to give similar values to the paediatric sensor [43]. It is thus certain that despite same sensor geometry and LED wavelengths, the INVOS adult sensor gives systematically lower values than the comparable neonatal and paediatric sensors.…”
Section: Discussionmentioning
confidence: 70%
“…(3)]. The rStO 2 estimate of NIRO-300 has been shown to estimate lower baseline values compared to other devices in neonates 34 and on the adult forearm. 35 Also, a study in a blood-lipid phantom revealed significant difference in rStO 2 estimates between three commercial devices, including the NIRO-300.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%
“…The differences are likely explained by the characteristics of the reported populations (e.g., GA, PA, specific morbidity), duration of measurements, and small sample sizes (9)(10)(11)(17)(18)(19)(20). It seems likely that the rScO 2 will either stabilize or may even increase again after 72 h (12,13,15,21 (15,20,21).It is noteworthy how close the −2 SD bands (i.e., p2.3) are to the rScO 2 threshold (i.e., 33-44%) reported to be associated with functional impairment of the brain (22,23). A lower CBF, either regional or global, in infants with a lower GA is the most plausible explanation for the positive association between GA and rScO 2 .…”
mentioning
confidence: 99%